Turmeric and cinnamon dominate in antioxidant potential among four major spices - Saranya, B; Sulfikarali, T; Chindhu, S; Muneeb, A M; Leela, N K; Zachariah, T J (Journal of Spices and Aromatic Crops, 2017)
Antioxidant activity of sequential extracts of black pepper, ginger, turmeric and cinnamon was determined by DPPH assay, phosphomolybdate method and ferric reducing power method and compared with that of the synthetic antioxidant BHA. The results revealed that methanol extract of cinnamon has highest antioxidant potential followed by chloroform extract of turmeric. The antioxidant potential was also correlated with total phenol content.